EXPLORE THE PHYSICAL EDUCATION TEACHING AND LEARNING PROCESS FOR LEARNER WITH INTELLECTUAL DISABILITY AND ITS OUTCOMES: A SYSTEMATIC REVIEW - Ding Lei; Adenan Ayob; Mohd Rain Shaari; Zulkeflee Yaacob (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
This study aims to explore the primary school physical education teaching and learning process for learner with intellectual disability and its outcomes. Educational inclusion has experienced significant changes when special-needs schools were largely focused on giving instruction to the intellectual disability. Narrative development takes place in an environment of historical turning points and legislative changes, and it emphasizes world-wide dedication to offering top-notch education to all of its residents, regardless of their particular requirements and difficulties. The special education environment in the nation has changed throughout time, bringing in an era of inclusion and catering to the various learning requirements of student with disability. The first objective of this study is to explore the primary school physical education teaching and learning process for learner with intellectual disability. The second objective is to explore the outcomes of primary school physical education teaching and learning process for learner with intellectual disability. The exploring is concerned on the platform of systematic literature review (SLR). Text analysis is done as a method that align to SLR. The finding that based on the first research question shows that physical education offers a wide range of advantages that go beyond physical health and include the improvement of cognitive, social includes environmental, and emotional skills. There are many benefits of physical education for students with disability are explored in this portion of the literature study. It highlights the connection between physical activity and higher motor abilities, self-esteem, social relationships, and general well-being. From the second research question, the findings show that via the quantitative and qualitative research design, respectively the results are mostly significant, and the phenomenon are varied that based on the specific thematic coding. As an implication, the researcher needs to understand the cultural context of how intellectual disability is defined in different perspectives. It is imperative that research in all countries be driven by local initiatives.